Congenital diaphragmatic hernias: Severe defect grade predicts the need for fundoplication. Issue 49 (4th December 2020) - Guglielmetti, Laura C.; Estrada, Arturo E.; Phillips, Ryan; Staerkle, Ralph F.; Gien, Jason; Kinsella, John P.; Liechty, Kenneth W.; Marwan, Ahmed I.; Vuille-dit-Bille, Raphael N.
Abstract : Abstract: Over one-third of infants with congenital diaphragmatic hernia (CDH) eventually require a Nissen fundoplication (NF). We examined pre- and intraoperative predictors for need of a NF in children undergoing CDH repair to elucidate, which patients will need a later NF. A retrospective analysis of all consecutive patients undergoing CDH repair at our institution from 2008 to 2018 was performed. Patients who underwent a NF were compared to those who did not (noNissen). Logistic regression analysis was performed to find independent predictors for NF in patients undergoing CDH repair. Severe Defect Grade was defined as defect >50% of the hemidiaphragm and intrathoracic liver. One hundred twenty-six patients were included, 42 (33%) underwent NF at a median of 61 days after CDH repair. Intrathoracic liver was more frequent in the NF (71%) versus noNissen (45%) group ( P  = .008). Absence of >50% of the hemidiaphragm was more frequent in the NF group (76% vs 31%, P  < .001). Severe Defect Grade emerged as independent predictor for NF (odds ratio 7, 95% confidence interval 3–16, P  < .001). Severe Defect Grade emerged as independent predictor for NF after CDH repair. Abstract : Supplemental Digital Content is available in the text